Science Diplomacy for Climate Action and Sustainable Development in Latin America and the Caribbean: How Important Is the Early Career Perspective to New Governance? - Cuellar-Ramirez, Palmira (Frontiers in Research Metrics and Analytics, 2021)
Science diplomacy and science-policy interface are tools that science has to address the biggest challenges that the world faces today. Scientific community needs to develop capacity building to bring these scientific knowledge to society and decision makers for a new governance of the Earth System and a more resilient society. Climate change is one of the most challenging issues and the Latin America and Caribbean (LAC) region is highly vulnerable to its consequences, particularly because it is expected to exacerbate environmental, social, and economic problems in the LAC region. In this context, and as an emergency call to address the climate crisis with the latest available science in the region, this paper collects a series of examples of the progress, best practices, gaps, challenges and solutions. We do so from the perspective of Early Careers Researchers (ECRs) and undergraduate and graduate students, highlighting what we are doing to engage scientists in society-policy-science interaction for sustainable development agenda and climate action in Latin America and the Caribbean